Intra-subunit flexibility underlies activation and allosteric modulation of neuronal nicotinic acetylcholine receptors - Chrisman, Paul A. (2013)
Allosteric modulation is a general feature of nicotinic acetylcholine receptors, yet the structural components and movements important for conversions among functional states are not well understood. In this study, we examine the communication between the binding sites for agonist and the modulator morantel (Mor) of neuronal α3β2 receptors, measuring evoked currents of receptors expressed in Xenopus oocytes with the two-electrode voltage-clamp method. We hypothesized that movement along an interface of β sheets connecting the agonist and modulator sites is necessary for allosteric modulation. To address this, we created pairs of substituted cysteines that span the cleft formed where the outer β sheet meets the β sheet constituting the (−)-face of the α3 subunit; the three pairs were L158C-A179C, L158C-G181C and L158C-K183C. Employing a disulfide trapping approach in which bonds are formed between neighboring cysteines under oxidation conditions, we found that oxidation treatments decreased the amplitude of currents evoked by either the agonist (ACh) or co-applied agonist and modulator (ACh + Mor), by as much as 51%, consistent with the introduced bond decreasing channel efficacy. Reduction treatment increased evoked currents up to 89%. The magnitude of the oxidation effects depended on whether agonists were present during oxidation and on the cysteine pair. Additionally, the cysteine mutations themselves decreased Mor potentiation, implicating these residues in modulation. Our findings suggest that these β sheets in the α3 subunit move with respect to each other during activation and modulation, and the residues studied highlight the contribution of this intramolecular allosteric pathway to receptor function.